Impairment of Mitochondrial Redox Status in Peripheral Lymphocytes of Multiple Sclerosis Patients - Gonzalo, Hugo; Nogueras, Lara; Gil-Sánchez, Anna; Hervás, José Vicente; Valcheva, Petya; González-Mingot, Cristina; Martin-Gari, Meritxell; Canudes, Marc; Peralta, Silvia; Solana, Maria José; Pamplona, Reinald; Portero-Otin, Manuel; et al. (Frontiers in Neuroscience, 2019)
Literature suggest that oxidative stress (OS) may be involved in the multiple sclerosis (MS) pathogenesis, in which the immune system is known to play a key role. However, to date, the OS in peripheral lymphocytes and its contribution to the disease remain unknown. The aim of the present study was to explore the influence of OS in peripheral lymphocytes of MS patients. To that end, a cross-sectional, observational pilot study was conducted (n = 58: 34 MS and 24 healthy subjects [control group]). We have measure superoxide production and protein mitochondrial complex levels in peripheral blood mononuclear cells (PBMCs) isolated from MS patients and control. Lactate levels and the antioxidant capacity were determined in plasma. We adjusted the comparisons between study groups by age, sex and cell count according to case. Results demonstrated that PBMCs, specifically T cells, from MS patients exhibited significantly increased superoxide anion production compared to control group (p = 0.027 and p = 0.041 respectively). Increased superoxide production in PBMCs was maintained after the adjustment (p = 0.044). Regarding mitochondrial proteins, we observe a significant decrease in the representative proteins content of the mitochondrial respiratory chain complexes I-V in PBMCs of MS patients (p = 0.002, p = 0.037, p = 0.03, p = 0.044 and p = 0.051, respectively), which was maintained for complexes I, III and V after the adjustment (p = 0.026; p = 0.033; p = 0.033, respectively). In MS patients, a trend towards increased plasma lactate concentration was detected (8.04 mg lactate/dL [5.25, 9.49] in the control group, 11.36 mg lactate/dL [5.41, 14.81] in MS patients) that was statistically significant after the adjustment (p = 0.013). This might be indicative of compromised mitochondrial function. Finally, antioxidant capacity was also decreased in plasma from MS patients, both before (p = 0.027) and after adjusting for sex and age (p = 0.006). Our findings demonstrate that PBMCs of MS patients show impaired mitochondrial redox status and deficient antioxidant capacity. These results demonstrate for first time the existence of mitochondrial alterations in the cells immune cells of MS patients already at the peripheral level.